Design and Build a New Student Registration Information System Supported by SMS Gateway at Alhira Middle School - Afero, Yosdarso (Knowbase : International Journal of Knowledge in Database, 2021)
This study aims to design a Web-Based Online Registration Information System Supported by SMS (Short Message Service) Gateway at Alhira Middle School that is valid, practical, and effective. The process of registering new students, which has been taking place at Alhira Junior High School, has not yet run online; this can be seen from the data process, report generation that still uses Ms. Office Word, and use paper archives. It makes data security not guaranteed, allowing much data to be lost. On the other hand, for prospective registrants who want to know information related to schools, it is still difficult to do, because it requires prospective registrants to come or visit the hut directly. Another problem is that more prospective new students come from outside the Tanah Datar area, of course, it requires a lot of costs, especially transportation. This problem is the background of this research. The type of research used is Research and Development, with the 4-D model stands for Define, Design, Develop and Disseminate. While the system development model used adopts the SDLC cycle (System Development Life Cycle, namely the waterfall model. The results of this study are a new student registration information system that has been tested for products including validity, practicality and effectiveness tests. The results of the validity test were carried out on three people; the validator obtained a total score of 0.88 with very valid criteria, the practicality test was carried out on three validators obtaining a total value of 93.33 with very practical criteria, and the effective value for ten respondents obtained a total result of 0.79 with very effective criteria. After testing the product, this information system can be declared feasible and can be used in the process of accepting new students at Alhira Middle School.